Fundamentals of smallholder irrigation: the structured system concept - Albinson, B.; Perry, C.J. (International Water Management Institute, 2002)
This study uses both farmer surveys and physical measurements to understand the impact RCTs have had on water use and water savings in the irrigated Rice-Wheat Zone of Pakistan's Punjab province. The findings show that field scale water savings achieved from RCTs is not necessarily equivalent to water savings at broader scales and may even result in an increase in overall water depletion.